Reality Check! Perceptions of MTV’s Jersey Shore and 16 and Pregnant/Teen Mom and Dating Violence Attitudes and Experiences - Rodenhizer, Kara Anne E. (Journal of interpersonal violence, 2021)
We examined college women’s (N = 354) perceptions of Jersey Shore and 16 and Pregnant/Teen Mom and how these perceptions are related to dating violence (DV) attitudes and behaviors. Although most DV attitudes and behaviors did not relate to frequency of viewing these shows, DV victimization was related to more frequent viewing of Jersey Shore. Moreover, DV perpetration and victimization was related to perceptions that the Jersey Shore was a fun show to watch, and accepting attitudes toward DV was inversely related to perceptions that Jersey Shore was offensive. Content analysis of open-ended responses regarding young women’s opinions about the shows’ portrayal of DV showed that most participants believed that Jersey Shore and 16 and Pregnant/Teen Mom depicted DV, although there was variability in how accurate these portrayals were perceived to be. Similarly, young women had varying opinions about how acceptable it was to portray DV on television as well as the extent to which MTV was doing enough to ensure that the individuals on the show received help for their experiences. Findings suggest the importance of helping viewers understand how the media influences their own beliefs and behaviors in dating and sexual relationships.